2018
DOI: 10.1021/acs.cgd.7b01634
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Amorphous Calcium Carbonate and Its Transformation Mechanism to Crystalline CaCO3 in Laminar Microfluidics

Abstract: For traditional experimental methods, the dynamic formation and transformation of amorphous calcium carbonate (ACC) are hard to capture due to its metastability and ease of transforming rapidly to the more stable phase. The emergence of microfluidic technology provides an effective approach on that issue, thus attracting widespread researchers' interest in crystallization research. In this study, based on laminar microfluidics, we demonstrate a microfluidic approach toward the study of the formation and transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…For precipitation reactions, the flow rate decides not only the width of the diffusive layer, but‐in some cases‐also the product composition. For example, Zeng et al . have reported that the crystallization of CaCO 3 is dependent on the volumetric flow rate Q .…”
Section: Methodology Of Microfluidics With Laminar Co‐flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…For precipitation reactions, the flow rate decides not only the width of the diffusive layer, but‐in some cases‐also the product composition. For example, Zeng et al . have reported that the crystallization of CaCO 3 is dependent on the volumetric flow rate Q .…”
Section: Methodology Of Microfluidics With Laminar Co‐flowsmentioning
confidence: 99%
“…Zeng et al. have studied the transition from amorphous to crystalline calcium carbonate precipitate through dissolution‐recrystallization processes at the interface of equimolar aqueous solutions of CaCl 2 and Na 2 CO 3 . A mixture of vaterite and calcite was observed in the channel and shows distributional variations along the channel, that is, a decreasing ratio of vaterite to calcite from the Y‐junction to the outflow port.…”
Section: Making Mineral Membranes In Microfluidic Devicesmentioning
confidence: 99%
“…Gong et al's research provided a new approach to biomimetic crystallization by using crystal hotels [26]. Zeng et al's work demonstrated a microfluidic approach towards the study of the formation and transformation of ACC (amorphous calcium carbonate) by using microfluidic technology [27]. However, these experiments were mainly carried out in microfluidic chips, which constrained the methods of characterization and hindered the use of high-throughput experiments.…”
Section: Of 11mentioning
confidence: 99%
“…37 The confinement due to the microfluidic conditions slows down the conversion of the unstable amorphous calcium carbonate into the crystalline form as opposed to the well-stirred reaction where the stable crystalline form appears within seconds to minutes of mixing. [38][39][40] Building upon the versatile applicability of microfluidics, we first study experimentally the precipitation of lithium phosphate in a microchannel and study the effect of flow on the growth of the precipitate particles. The results are then corroborated by simple calculations.…”
Section: Introductionmentioning
confidence: 99%